A discriminatory diagram of massive versus stratified deposits based on the sedimentation and bedload transportation rates. Experimental investigation and application to pyroclastic density currents. Issue 4 (24th January 2020) - Dellino, Pierfrancesco; Dioguardi, Fabio; Doronzo, Domenico Maria; Mele, Daniela
Abstract: Dense gas‐particle jets similar to collapsing eruption columns were generated by large‐scale experiments. The column collapse resulted in a ground‐hugging current forming stratified layers with bedding similar to natural pyroclastic density current deposits. At the impact of the collapsing column on the ground, a thick, massive bed was formed due to a high sedimentation rate that dumped turbulence due to high clast concentration. Down‐current, flow expansion favoured turbulence and dilute gas‐particle current that formed thin rippled layers deposited under traction. Experiments fed with fine ash (median size 0·066 mm) formed deposits without tractional structures, because fine particles, as other sedimentary fine material, is cohesive and exposes a limited surface to the shear stress. Experimental outcomes show that massive beds are formed where the sedimentation rate per unit width S rw exceeds the bedload transportation rate Q b by two orders of magnitude. A lower ratio generates traction at the base of the flow and formation of shear structures that increase in wavelength and height with a decreasing flux. This study presents a diagram that provides a useful addition for facies analysis of pyroclastic density currents, provided that deposits representing sustained sedimentation can be identified in the field. In the diagram a decrease in the S rw / Q b ratio corresponds to an increase in bedform size. Application of the diagram for hazard assessment purposes allows the reconstruction of the mass eruption rate of the Agnano–Monte Spina eruption at Campi Flegrei, which is the main variable defining the intensity of past eruptions, and of the Bingham rheology of the massive underflow of the Mercato pyroclastic density current at Vesuvius.